A Review of Iron Overload in Beta-Thalassemia Major, and a Discussion on Alternative Potent Iron Chelation Targets. (May 2022) - Yadav, Piyush Kumar; Singh, Ajay Kumar
For years, arrhythmias have been well documented in the medical arena as a cardiovascular consequence of iron overload (IO). They are thought to be linked to the accumulation of iron in the myocardium. Iron is the earth's fourth most abundant element and the second most plentiful metal (after aluminium). When it comes to biology, iron fills two roles: it's necessary and it's poisonous. It is necessary as a trace iron element since it is found in hemoproteins such as haemo-globin, but it is poisonous in excess amounts of the ability to produce free radicals, which can harm the biological system. The high prevalence of cardiomyopathy in patients with hemosiderosis, particularly in cases of transfusional iron overload, strongly suggests that iron deposition in the heart plays a key role in the development of heart failure. Thalassemia major, which necessitates blood transfusion as a treatment, absorbs a large amount of iron in the patient's duodenum. Moreover, Iron Overload causes a threat to vital organs such as the liver and, initiates events of the pathologic progression involving apoptosis, fibrosis, and ultimately cardiac dysfunction. Furthermore, we discuss the iron overload issue as it relates to beta-thalassemia major patient blood transfusion treatment, as well as key individuals accountable for iron excess that ultimately leads to cardiomyopathy.